Histopathological Evaluation of Erythropoietin's Protective Effect Against Doxorubicin-Induced Hepatotoxicity - Zeena Jasim Saddam; Yassir Mustafa Kamal; Huda Jaber Waheed; Gaber El-Saber Batih (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
Doxorubicin is an effective broad-spectrum anticancer drug; however, hepatotoxicity limits its clinical usage. Erythropoietin, a glycoprotein hormone primarily recognized for its crucial function in promoting erythropoiesis. Recently, it has been shown that it possesses significant cytoprotective effects in several organs, including the liver, heart, and brain.